Правосудие не может быть рекомендательным - Абдуллоев, Ф.А. (Держава і право, 2011)
Приведенная
автором
правовая
позиция
о юридической
силе
решений
Экономического
Суда
СНГ по делам
о межгосударственных
экономических
спорах
в рамках
двух
международных
организаций
– СНГ и ЕврАзЭС
основывается
на системном
и сравнительном
анализе
положений
статутных
документов
Экономического
Суда
СНГ и норм
международного
права.
Актуальность
исследования
обусловлена
неоднозначным
пониманием
данного
вопроса,
имеющего
принципиальное
значение
для обеспечения
единообразного
применения
соглашений
государств
Содружества
и Евразийского
экономического
сообщества
и основанных
на них экономических
обязательств. Legal position highlighted in this article concerning judicial force of Economic Court
decisions on interstate economic disputes in the framework of two international organizations
– CIS and EurAsEC – is based on systems and comparative analysis of the provisions of
statute documents of CIS Economic Court and international law regulations. Value of this
research is due to the difference of points of view on this issue, that have fundamental importance
for ensuring the unified approach to the application of agreements adopted within the
Commonwealth of Independent States and Eurasian Economic Community and execution of
the economic obligations provided by these agreements.